If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(3x + 2)(3x + -2) = 0 Reorder the terms: X(2 + 3x)(3x + -2) = 0 Reorder the terms: X(2 + 3x)(-2 + 3x) = 0 Multiply (2 + 3x) * (-2 + 3x) X(2(-2 + 3x) + 3x * (-2 + 3x)) = 0 X((-2 * 2 + 3x * 2) + 3x * (-2 + 3x)) = 0 X((-4 + 6x) + 3x * (-2 + 3x)) = 0 X(-4 + 6x + (-2 * 3x + 3x * 3x)) = 0 X(-4 + 6x + (-6x + 9x2)) = 0 Combine like terms: 6x + -6x = 0 X(-4 + 0 + 9x2) = 0 X(-4 + 9x2) = 0 (-4 * X + 9x2 * X) = 0 (-4X + 9x2X) = 0 Solving -4X + 9x2X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'X'. X(-4 + 9x2) = 0 Factor a difference between two squares. X((2 + 3x)(-2 + 3x)) = 0Subproblem 1
Set the factor 'X' equal to zero and attempt to solve: Simplifying X = 0 Solving X = 0 Move all terms containing X to the left, all other terms to the right. Simplifying X = 0Subproblem 2
Set the factor '(2 + 3x)' equal to zero and attempt to solve: Simplifying 2 + 3x = 0 Solving 2 + 3x = 0 Move all terms containing X to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = 0 + -2 3x = 0 + -2 Combine like terms: 0 + -2 = -2 3x = -2 Add '-3x' to each side of the equation. 3x + -3x = -2 + -3x Combine like terms: 3x + -3x = 0 0 = -2 + -3x Simplifying 0 = -2 + -3x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 3
Set the factor '(-2 + 3x)' equal to zero and attempt to solve: Simplifying -2 + 3x = 0 Solving -2 + 3x = 0 Move all terms containing X to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 3x = 0 + 2 3x = 0 + 2 Combine like terms: 0 + 2 = 2 3x = 2 Add '-3x' to each side of the equation. 3x + -3x = 2 + -3x Combine like terms: 3x + -3x = 0 0 = 2 + -3x Simplifying 0 = 2 + -3x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
X = {0}
| 56/G=7 | | 18n^2+102n-168=0 | | 5x+26=3+8x-7 | | 7+4=2(7+-5) | | 4s-3(s+4)=2(w+5)+4 | | 12/5=3/x | | -3/8-13/8+1=5 | | 4/a-3=2/5 | | -13/8m-3/8m+1=5 | | 56x^2-15x-54=0 | | 0.6x-7.5(x-1)=42 | | b^2+1=-3 | | 10c^2-33cd+20d^2= | | 4s+3p=20 | | 10x-13=3y | | 2(h-1)=-3(h+12)-11 | | 6-x/2=2 | | Fx=10x-5 | | 3x+x+5x=72 | | -5=n/9-4 | | 14x^2-116x+32=0 | | -15*x^2= | | 8x^6-27y^6=0 | | (3/8)*72 | | 45/6-3i | | 2(3a-5)+2a=70 | | 32-3h=5h+8 | | -13=5(1+4m)+2 | | -13x-12=-129 | | 5(3-2)+8=43 | | 2n-3n=0-5 | | v^2-2=98 |